Analisis peran guru dalam meningkatkan motivasi belajar siswa kelas iii sekolah dasar pada masa pandemi covid-19 - Rahmantri, Cikita; Kurniawan, Sandra Bayu; Budiharto, Tri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
The results of this study indicate that during the pandemic students' learning motivation decreases. If this is allowed to continue, it will have a negative impact on the future of Indonesian education. So it takes the role of the educator as a teacher and as a motivator in various ways so that it is expected to be able to increase student learning motivation. Based on the research that has been done and the explanations presented, it can be concluded that there are several roles played by the teacher in increasing the learning motivation of the students of SD Negeri Setono during the covid-19 pandemic, including 1) the teacher as a demonstrator, the teacher always studies and prepares material. 2) The educator as a class manager, the teacher creates a comfortable atmosphere and conducts active learning. 3) The teacher, as a mediator, the teacher chooses the learning media according to the student's learning needs. 4) teachers as facilitators, teachers understand and provide facilities to students. 5) the teacher as an evaluator, the educator evaluates by giving assignments, holding tests, and giving homework. 6) the teacher as a motivator, instils a sense of enthusiasm and also provides motivation in various ways .